PREVALANCE OF HEPATITIS C VIRUS ANTIBODIES IN DIFFERENT GROUPS - Hüseyin TURGUT; Mine TURHANOĞLU; Kemalettin AYDIN; Eralp ARIKAN; Halil DEĞERTEKİN and Sedat ARITÜRK (Turkish Journal of Gastroenterology, 2020)
-